Investigation of the electrical quality and long-term stability of aluminum ground stud connections in automotive applications - Haak, Viktor; Yang, Keke; Meschut, Gerson (Journal of Advanced Joining Processes)
The rapid advancement in the electrification of modern vehicles has led to a continuous increase in electrical consumers for various comfort and safety functions. Ground studs serve as the electrical interface between the conductive vehicle body and the onboard network. Drawn arc stud welding is an economical and established joining process for producing ground stud joints. The circuits in the onboard network are increasingly subject to greater demands regarding current-carrying capacity and long-term stability. Reliable signal and power transmission require minimal contact resistance at the electrical connection points of the ground stud system and must withstand various operating and environmental conditions over the entire service life. In this study, a ground stud made of AlMg5, with a ZnNi-coated steel cap nut was used on a 2.0 mm thick sheet of AlMg3. The electrical connection of the ground studs was made using tinned copper cable lugs and 35 mm² cables. To analyze the electrical resistance behavior in an accelerated test, the ground studs were subjected to a superimposed load with a cyclic current profile for 1008 hours under changing climatic conditions. The results show that under the chosen operational and environmental conditions, accelerated aging and intermittent resistance behavior occur. A characteristic drop in resistance during the test indicates the failure point of the electrical connection. The cause of failure can be attributed to media penetration into the electrical contact zone. A failure of the electrical connection was observed after 512 hours.
Keywords: Stud welding; aluminum grounding connection; electrical resistance; superimposed load